2021
DOI: 10.5005/jp-journals-10071-23917
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Blood Gas as a Predictor of Mortality in COVID Pneumonia Patients Initiated on Noninvasive Mechanical Ventilation: A Retrospective Analysis

Abstract: Background: The alveolar–arterial oxygen (A–a) gradient measures the difference between the oxygen concentration in alveoli and the arterial system, which has considerable clinical utility. Materials and methods: It was a retrospective, observational cohort study involving the analysis of patients diagnosed with acute COVID pneumonia and required noninvasive mechanical ventilation (NIV) over a period of 3 months. The primary objective was to investigate the utility of the A–a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…14 More directly a retrospective study on 165 covid subjects requiring NIMV showed that PaCO 2 levels are significantly lower in nonsurvivors. 15 Similarly, in a previous study we showed that the ratio between PaCO 2 levels and the fraction of inspired oxygen was able to predict the need for invasive mechanical ventilation independently from several already known predictors of severe disease. 16 In line with these studies, that indirectly demonstrated the predictive role of clinical worsening of hypocapnia, our data prospectively highlight its potential role in predicting the need for NIMV in a patient population entering the emergency department for acute respiratory failure related to SARS-CoV-2 infection, independently of a number of confounding factors.…”
Section: Articlesupporting
confidence: 56%
“…14 More directly a retrospective study on 165 covid subjects requiring NIMV showed that PaCO 2 levels are significantly lower in nonsurvivors. 15 Similarly, in a previous study we showed that the ratio between PaCO 2 levels and the fraction of inspired oxygen was able to predict the need for invasive mechanical ventilation independently from several already known predictors of severe disease. 16 In line with these studies, that indirectly demonstrated the predictive role of clinical worsening of hypocapnia, our data prospectively highlight its potential role in predicting the need for NIMV in a patient population entering the emergency department for acute respiratory failure related to SARS-CoV-2 infection, independently of a number of confounding factors.…”
Section: Articlesupporting
confidence: 56%
“…Для Анализ КОС и газов крови является важным способом оценки состояния пациента в ОРИТ. В нескольких исследованиях подтверждено, что рО₂ и рСО₂ в артериальной крови могут быть предикторами летального исхода в той или иной степени [11]. Вместе с тем они, как и значения рН, не вошли в мета-анализы значимых предикторов исхода COVID-19 [12,13].…”
Section: рис 3 сравнение различных клинических баз по средним значени...unclassified